2023
DOI: 10.3390/microorganisms11082018
|View full text |Cite
|
Sign up to set email alerts
|

Current Insights into the Use of Probiotics and Fatty Acids in Alleviating Depression

Abstract: (1) Background: Depression is the most prevalent psychiatric symptom present among individuals of all ages and backgrounds, impacting an estimated 300 million people globally. Therefore, it demands a significant amount of attention when it comes to managing depression. A growing amount of data reveal that probiotics and fatty acids could be beneficial to depression. However, the opposing position maintains that they have no influence on depression. A network meta-analyses of existing datasets aid in the estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 114 publications
0
1
0
Order By: Relevance
“…Four weeks of GOS treatment reduced self-reported anxiety scores in highly anxious participants [ 190 ]. A meta-analysis showed that the use of polyunsaturated fatty acids alleviates depressive symptoms in humans [ 191 , 192 ]. Water-soluble cellulose acetate, which is fermented by intestinal bacteria and increases the production of short-chain fatty acids and GABA in the human gut, has the potential to be a prebiotic [ 193 ].…”
Section: Approaches To Restoration Of the Gut Microbiota In Depressionmentioning
confidence: 99%
“…Four weeks of GOS treatment reduced self-reported anxiety scores in highly anxious participants [ 190 ]. A meta-analysis showed that the use of polyunsaturated fatty acids alleviates depressive symptoms in humans [ 191 , 192 ]. Water-soluble cellulose acetate, which is fermented by intestinal bacteria and increases the production of short-chain fatty acids and GABA in the human gut, has the potential to be a prebiotic [ 193 ].…”
Section: Approaches To Restoration Of the Gut Microbiota In Depressionmentioning
confidence: 99%